Criterios para la clasificación y descripción de movimientos en masa (2000)
A mass movement may be defined as any lithologic or debris material displacement downwards (vertical or in the direction of a slope foot), caused by gravity. In common language, there are other synonymous words such as: landslide, collapse and terrain movement.The occurrence of a mass movement develops some characteristic geomorphologic and morphometric features. The morphologic elements may be associated to displaced mass or surrounding intact terrain. Among these morphologic elements are the crown, the main scarp, the rupture surface, the body, the flanks, the front and the foot.Mass movements have been internationally classified in eight basic types: fallings, flows, landslides, lateral propagation, collapses, reptation, torrential floods, avalanches and complex mass movements. Nevertheless, they may be described or classified under many points of view, including: relative displacement, velocity or movement rate, type and size of involved material, relative activity, relative dimension, grade of development, transport mechanism, genesis and detonate agent.Mass movements may be quantified for their magnitude in relation to the volume, activity, velocity and intensity according to damages occasioned.